DINAMIKA KETAHANAN MASYARAKAT DI DESA TENGGELAM: ANALISIS PEOPLE-PLACE-INSTITUTION DI PESISIR DEMAK, INDONESIA - Esa Linita Br Sitepu; S Sariffuddin (Jurnal Pengembangan Kota, 2024)
This study examines the resilience of communities living in sinking villages along the northern coast of Java, Indonesia — an extreme phenomenon in which settlements gradually subside and disappear due to coastal erosion and chronic tidal flooding. Resilience is viewed as a multidimensional phenomenon that should be assessed across three components: people, place, and institutions. Using this framework, the study evaluates how well communities can adapt and survive amid worsening environmental conditions. Based on descriptive statistics and a scoring method, the study shows that over the past 30 years, these villages have been gradually sinking, with flood depths now exceeding 1 meter. Field observations reveal that residents cope by elevating their houses up to 1.5 meters. At the same time, local governments and community groups also invest in public infrastructure, such as roads, and develop joint disaster risk reduction initiatives. The assessment identifies three levels of community resilience: low, medium, and high. The people dimension emerges as the main factor differentiating communities, especially in terms of preparedness, livelihood types, and prior disaster experiences. Meanwhile, the place dimension demonstrates resilience through community participation and environmental programs that raise awareness and strengthen collective capacity to face increasingly permanent sinking conditions.